2000
DOI: 10.1007/bf02492826
|View full text |Cite
|
Sign up to set email alerts
|

Study of biologically active amines in grapes and wines by HPLC

Abstract: SummaryThe biologically active amines agmatine, cadaverine, histamine, phenethylamine, putrescine, spermidine, and tyramine have been determined in different varieties of grape, aszu grape, wine and aszu wine from the Tokaj region of Hungary. Ion pairs formed between the amines and octanesulphonic acid were separated by liquid chromatography on a #Bondapak C18 reversed-phase column, and spectrofluorimetric detection was performed after post-column derivatization with o-phthalaldehyde and 2-mercaptoethanol. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 9 publications
5
30
0
Order By: Relevance
“…The presence of putrescine in grape juices, as well as cadaverine, spermine, and spermidine, was also reported by Bauza et al (1995) and Sass-Kiss et al (2000). Bover-Cid et al (2006) A distinction among the juices was observed according to PCA scores: principal component 1 (PC1) explained close to 60% of the variance and distributed juices from 'Isabel Precoce' grapes to the left and from 'BRS Cora' to the right of the score plot (Figure 1).…”
Section: Resultssupporting
confidence: 79%
“…The presence of putrescine in grape juices, as well as cadaverine, spermine, and spermidine, was also reported by Bauza et al (1995) and Sass-Kiss et al (2000). Bover-Cid et al (2006) A distinction among the juices was observed according to PCA scores: principal component 1 (PC1) explained close to 60% of the variance and distributed juices from 'Isabel Precoce' grapes to the left and from 'BRS Cora' to the right of the score plot (Figure 1).…”
Section: Resultssupporting
confidence: 79%
“…Some amines are normal constituents of grapes with amounts varying with variety, soil type and composition, fertilization and climatic conditions during growth and degree of maturation. Putrescine and spermidine are usually abundant in grapes, whereas agmatine, cadaverine, spermine, histamine, tyramine and phenylethylamine have been found in small amounts (Ough, 1971;Zee et al, 1983;Vidal-Carou et al, 1990;Glória et al, 1998;Hajós et al, 2000;Sass-Kiss et al, 2000). Besides the amines already present in grapes, several can be formed and accumulate during wine making.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of these amines was also observed in Rioja wines (Vazquez-Lasa et al, 1998). Prevalence of other types of amines has also been reported in the literature, for example, 2-phenylethylamine in wines from Hungary Sass-Kiss et al, 2000). Histamine, tyramine and putrescine contents in Brazilian wines were lower compared to the red wines from other countries (Solange et al, 2005).…”
Section: Geographical Origin Variety Viticultural Practices and Vinmentioning
confidence: 81%
“…Some amines are frequent constituents of grapes with amounts varying with variety, soil type and composition, fertilization and climatic conditions during the grape growth and stage of maturation (Souza et al, 2005). Putrescine and spermidine are usually abundant in grapes, whereas agmatine, cadaverine, spermine, histamine, tyramine and phenylethylamine have been found in small amounts (Ough, 1971;Zee et al, 1983;Vidal-Carou et al, 1990;Glória et al, 1998;Hajos et al, 2000;Sass-Kiss et al, 2000).…”
Section: Biogenic Amines (Ba)mentioning
confidence: 99%